Resolution, access, and waiting time for specialties in different models of care - Rosa Mori, Natália Leite [UNESP]; Neto, Jaime Olbrich [UNESP]; Spagnuolo, Regina Stella [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
OBJECTIVE: This study aimed to identify the treatment demands coming from primary health care units and, based on that, the demand for referrals to medical specialties in reference services. This study is justified by the scarcity of scientific literature on the subject. METHODS: This is a cross-sectional study using secondary data on the treatments and referrals made by the primary health care units, throughout 2014, in a municipality of the State of Sao Paulo, Brazil. The total population treated in 2014 was considered, resulting in 411,177 treatments. RESULTS: Out of all treatments performed, the percentage of referrals was of 4.42%, showing that 95,58% of the problems did not need to be referred to another service. A number of 8,897 referrals were made, to 6,850 users, who were mostly women (60.74%). The mean of referrals per patient was 1.3 (min. 1 and max. 8), and 1,604 patients (23.5%) were referred at least twice. CONCLUSIONS: Primary health care services have been responsible for a large number of treatments, whereas the demand for referrals has decreased, suggesting that such services have established themselves as a gateway to the health system and achieved the expected solvability, although the waiting time for some specialties is very long.
Keywords: Ambulatory care facilities; Basic health services; Clinical decision-making; Health services needs and demands; Hospitals; Primary health care; Referral and consultation; Specialties